Sosialisasi Hukum Tentang Penghapusan Kekerasan dalam Rumah Tangga di Kelurahan Gedong Meneng Baru Kecamatan Rajabasa Kota Bandar Lampung - Akib, Muhammad; Sumarja, FX (Lembaga Penelitian dan Pengabdian Universitas Lampung, 2018)
Problems in this activity are: 1) Lack of knowledge or information received by society about Law of Domestic Violence; 2) Lack of legal understanding of the community about the content of the Law on Domestic Violence; 3) There is still violence in the household, which is not discovered. Problem solving is done by means of legal communication. Legal communication is the process of conveying messages in accordance with the law that the contents of a rule of law, with the aim of creating mutual understanding or understanding of the law, resulting in either a change of mind, attitude and behavior of recipients, without any coercion from outside. The results of the activities showed an increase understanding and knowledge of citizens related to the rules / laws governing the elimination of domestic violence, which was originally to have knowledge of the value of 55.25, after the project is implemented have knowledge of the value of 74.75. This kind of activity needs to be done for the future, to continuously provide understanding and knowledge related to the rules of community life.